Investigation of Elemental Composition in White Wine Treated with Varying Doses of Bentonite - Elisaveta Mladenova; Ivan Bakardzhiyski; Eva Dimitrova (Beverages)
The mineral composition of wine is affected by numerous factors, including treatments with bentonite to control colloidal hazes. In this study, 10 parallel samples of white wine (Chardonnay, 2021 vintage year) were treated with pre-selected bentonite (activated calcium bentonite) at increasing doses, from 0.3 to 3.0 g/L. Following acid mineralization, the content of some important elements was determined. The elements Al, Ba, Cd, Cu, Cr, Fe, Mg, Mn, P, Pb, and Zn were measured by inductively coupled plasma with optical emission spectrometry (ICP-OES), while flame atomic absorption spectrometry (FAAS) was used for the determination of Ca, K, and Li. Depending on the applied dose, the bentonite changed the concentration of the determined elements in different ways. Results indicated that higher doses of bentonite led to an increase in Al, Ca, and Fe content, while Cu and Zn initially rose with low doses before declining to near-baseline levels with higher doses.